2020
DOI: 10.7717/peerj.8488
|View full text |Cite
|
Sign up to set email alerts
|

Get a grip—evolution of claw shape in relation to microhabitat use in intertidal arthropods (Acari, Oribatida)

Abstract: Claws may be the most common biological attachment devices in animals but relatively few studies have examined the ecological and evolutionary significance of their morphology. We performed the first geometric morphometric investigation of arthropod claws using 15 intertidal oribatid mite species from two different families living in three different habitat types to determine if claw shape is correlated with ecology. Our results show that species living on rocky shores show remarkably high and strongly curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 30 publications
(47 reference statements)
6
29
0
Order By: Relevance
“…A phylogenetic signal is defined as ‘a tendency for related species to resemble each other more than they resemble species drawn at random from the tree’ 18 . In the case of intertidal oribatid mites, on the other hand, certain congeneric species clearly clustered in different ecological groups 12 indicating that ecology is the most important factor in shaping claws and that claw shapes contain little phylogenetic information. Nevertheless, the authors of this study 12 did not specifically test for a phylogenetic signal in their dataset, therefore, it remained uncertain if claw shape is mainly a result of ecological adaptation or just a result of closely related species showing similar ecologies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A phylogenetic signal is defined as ‘a tendency for related species to resemble each other more than they resemble species drawn at random from the tree’ 18 . In the case of intertidal oribatid mites, on the other hand, certain congeneric species clearly clustered in different ecological groups 12 indicating that ecology is the most important factor in shaping claws and that claw shapes contain little phylogenetic information. Nevertheless, the authors of this study 12 did not specifically test for a phylogenetic signal in their dataset, therefore, it remained uncertain if claw shape is mainly a result of ecological adaptation or just a result of closely related species showing similar ecologies.…”
Section: Introductionmentioning
confidence: 99%
“…Büscher and Gorb 11 performed a sophisticated study on the attachment devices of stick insects and demonstrated a complex complementary effect of claws and adhesive pads and that these structures correlated with substrate surface and hence with the ecology of the animals. Apart from this work, there was only a single study 12 demonstrating a possible correlation between claws and ecology in arthropods where these authors investigated mites. Mites represent the smallest arthropods and they occupy a wide range of ecological niches, which means the landscape microstructure is highly diverse for the different ecological groups 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These traits are chiefly specialised claws ( Figure S1d, S1e), which might aid in clinging to the leaf's surface and thereby withstand turbulence (e.g. Pfingstl, Kerschbaumer, & Shimano, 2020; but see Pugh, King, & Fordy, 1987) and a larger body size ( Figure S1g). In contrast, the assemblages in the matte consist of species bearing these traits, as well as species with more slender bodies ( Figure S1i) and a longer and pointier gnathosoma ( Figure S1j).…”
Section: Spatial Patterns In Functional Diversitymentioning
confidence: 99%